Optimization of AI Usage in Learning Materials Application of Prompt Engineering Techniques for Learning Management Systems (LMS) - Muhammad Fauzan Gustafi (JRST (Jurnal Riset Sains dan Teknologi), 2025)
The application of artificial intelligence (AI) in education opens new opportunities to enhance the quality and effectiveness of learning materials. This study integrates the capabilities of ChatGPT-4o with Prompt Engineering techniques, including persona, context, task, format, exemplar, and tone, to develop AI-based adaptive and interactive instructional content within Learning Management Systems (LMS). By employing these techniques, AI can generate more relevant, personalized, and academically aligned learning materials. The evaluation results using Mean Absolute Error (MAE) indicate that the error rate in generating learning outcomes is 17, syllabus design 14, quiz generation 12, and retrieval of CPL & CPMK 9. These values demonstrate that while ChatGPT-4o is reasonably accurate in generating instructional materials, deviations still exist, particularly in completeness of information and material specification. Furthermore, manual validation remains necessary to ensure alignment with academic standards. Thus, this study confirms that AI-based Prompt Engineering can be an effective and efficient tool for supporting digital learning, yet human supervision is essential to maintain accuracy, credibility, and the quality of educational content.